The Effects of High Intensity Progressive Resistance Training on Psychological Stress and Biochemicals Parameters - Arimi Fitri Mat Ludin; Lau, Hui Jin; Suhaniza Sairan; Mahadir Ahmad; Nor Farah Mohd Fauzi (Penerbit UKM, 2015)
Stress is a common problem among university students and studies showed that involvement in exercise could help in reducing stress. However, information regarding the effect of high intensity progressive resistance training (PRT) using a resistant tube on stress among inactive and moderate active young male university students is limited. Hence, the aim of this study is to examine the effect of high intensity PRT using a resistant tube on psychological stress level, cortisol, DHEA and physical fitness in this population. A total of 30 male university students were participated in this quasi-experiment study. Intervention group (n = 14, age: 21.50 ± 1.37 yr) was participaned to carry out high intensity PRT by using resistant tube 3 times per week for 10 weeks; control group (n = 16, age: 21.29 ± 1.86 yr) was asked to continue their current lifestyle as usual. Before and after 10 weeks of intervention, psychological stress was measured by using PSS and SLSI questionnaires; cortisol and DHEA level were measured by using ELISA method. Timed up-and-go (TUG) used to examine dynamic balance and handgrip strength test used to measure muscle strength. Findings showed that the increased of DHEA level after 10 weeks of intervention was significantly difference between control and intervention groups (p < 0.05). There was no significant group difference in changes over time in anthropometric and body composition measurements, stress scores, cortisol level and physical fitness. High intensity PRT using resistant tube may be beneficial in increasing DHEA level among young male adults, which can act as a stress biochemical indicator.